Measurement of D0, D+, D[star]+ and D+s production in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; et al. (Journal of high energy physics, 2018)
We report measurements of the production of prompt D0, D+, D*+ and D s + mesons in Pb-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN−−−√=5.02sNN=5.02 \sqrt{s_{NN}}=5.02 TeV, in the centrality classes 0-10%, 30-50% and 60-80%. The D-meson production yields are measured at mid-rapidity (|y| < 0.5) as a function of transverse momentum (pT). The pT intervals covered in central collisions are: 1 < pT< 50 GeV/c for D0, 2 < pT< 50GeV/c for D+, 3 < pT< 50GeV/c for D*+, and 4 < pT< 16GeV/c for D s + mesons. The nuclear modification factors (RAA) for non-strange D mesons (D0, D+, D*+) show minimum values of about 0.2 for pT = 6-10 GeV/c in the most central collisions and are compatible within uncertainties with those measured at s√NN=2.76sNN=2.76 {\sqrt{s}}_{NN}=2.76 TeV. For D s + mesons, the values of RAA are larger than those of non-strange D mesons, but compatible within uncertainties. In central collisions the average RAA of non-strange D mesons is compatible with that of charged particles for pT> 8 GeV/c, while it is larger at lower pT. The nuclear modification factors for strange and non-strange D mesons are also compared to theoretical models with different implementations of in-medium energy loss. Open image in new window
Im Titel wird "star" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel sind "0", "star" und "+" hochgestellt
Im Titel sind "+" und "s" untereinander geschrieben: "+" hochgestellt "s" tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, M.L. Knichel, L. Leardini, J. Mercado Pérez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]